The trend of the socio-economic development of the regions of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
Socio-economic development of the region is a multidimensional and multifaceted process which is usually considered in terms of the aggregate of various social and economic objectives. The level of development of regions determines the level of development of the country as a whole. In this regard, it is particularly important to identify major trends of regional development of the country. Today, the main economic activity is carried out in regions. They are allowed to independently solve economic problems, establish external economic and interregional connections. Each region of the Republic of Kazakhstan has inherent to it natural resources, peculiarities of their location, national and historical features, the structure of the economy, the level of economic development and specialization. The analysis of the socioeconomic development of the regions of Kazakhstan in recent years has revealed trends formed in both positive and negative directions.
Keywords: region; regional policy; indicators of socio-economic development of regions; gross regional product